Entrepreneurial Intentions: Theory of Planned Behavior Perspectives - Simatupang, Rintar Agus; Bajari, Makarius (KnE Social Sciences, 2021)
Rooted in this study are the important principles of enterprise and entrepreneurship, which raise important questions about how entrepreneurship education should be positioned institutionally. These questions address theoretical and philosophical challenges, strategic choices and institutional capacities. One of the programs of the Directorate General of Higher Education (DIKTI) of the Ministry of Education and Culture of the Republic of Indonesia, which is aimed at all state universities and several selected private universities, is the independent entrepreneurship program. This has been implemented in higher education to foster the entrepreneurial spirit and culture of Indonesian students. Participants in this study were students who had attended entrepreneurship training or were taking entrepreneurship courses at the Papua University Campus and at Dian Nuswantoro University, Semarang. The sampling method in this study was non-probability sampling with purposive sampling. The data collection was carried out by a survey. The data analysis was conducted using multiple linear regression analysis. The results of the study showed that the instrumentation readiness variable had a positive effect on entrepreneurial intentions, while the need for achievement and self-efficacy variables had no effect. Keywords: need for achievement, self-efficacy, instrumental readiness, entrepreneurial intentions